Case report on multiple solitary radiolucencies in the mandible - a diagnostic dilemma - D’souza, Valen Dela; Rao, Prasanna Kumar; Kini, Raghavendra (Journal of Oral Diagnosis, 2020)
Radiolucent mandibular lesions seen on panoramic radiographs develop from both odontogenic and non-odontogenic structures and represent a broad spectrum of lesions with a varying degree of malignant potential. Here, we report a case of a forty-five-year- old female patient with a complaint of pain and pus discharge from the left side of the face. Based on the characteristic clinical appearance, a diagnosis of chronic osteomyelitis was made. However, on digital panoramic radiography, a rather unusual radiolucent appearance in the ramus and coronoid process of the mandible was observed. Several laboratory investigations and advanced diagnostic imaging techniques were carried out to narrow down the differential diagnosis, which was crucial for the identification of this lesion which was diagnosed as Primary Intraosseous Carcinoma. The objective of this clinical case report is to highlight this unusual radiographic appearance to aid in future diagnosis.